1999
DOI: 10.1080/002689799164919
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field effect as a probe of distance-dependent electron transfer in systems undergoing free diffusion

Abstract: A theoretical analysis is presented of the problem of how distance-dependent electron transf er in photoinduced forward electron transfer followed by geminate backward electron transfer in liquid solution is re¯ected in the viscosity dependence of the magnetic ® eld e ect ( MFE) on the e ciency of free radical formation u ce in such reactions. The stochastic Liouville equation formalism is employed to model the reaction behaviour of distance-distributed, triplet-born radical pairs ( R Ps) undergoing free di us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…In such RIPs having a long D-A distance, the exchange interaction may be so small that ISC from the singlet to the triplet states is reduced by H, as shown in solution [27,28] and at crystal surfaces [29]. Since the population of the singlet RIPs relative to that of the triplet RIPs becomes higher in the presence of H, exciplex fluorescence reduced by F is recovered to some extent in the presence of H; E-F-I-Q of the exciplex fluorescence becomes less in the presence of H. As already mentioned, it is also considered that fluorescent exciplex in type (I) is formed not only from RIP produced by PIET but also from a contact pair of the LE state, i.e., (D*…A) in Figure 1, since E-F-I-Q of the LE fluorescence, which leads to E-F-I-E of the number of RIPs produced by PIET, does not induce an enhancement of the exciplex fluorescence [61].…”
Section: Discussionmentioning
confidence: 99%
“…In such RIPs having a long D-A distance, the exchange interaction may be so small that ISC from the singlet to the triplet states is reduced by H, as shown in solution [27,28] and at crystal surfaces [29]. Since the population of the singlet RIPs relative to that of the triplet RIPs becomes higher in the presence of H, exciplex fluorescence reduced by F is recovered to some extent in the presence of H; E-F-I-Q of the exciplex fluorescence becomes less in the presence of H. As already mentioned, it is also considered that fluorescent exciplex in type (I) is formed not only from RIP produced by PIET but also from a contact pair of the LE state, i.e., (D*…A) in Figure 1, since E-F-I-Q of the LE fluorescence, which leads to E-F-I-E of the number of RIPs produced by PIET, does not induce an enhancement of the exciplex fluorescence [61].…”
Section: Discussionmentioning
confidence: 99%
“…This is appropriate for some systems in zero or relatively small external magnetic fields. Otherwise the basis of the problem should be essentially extended and a more complex theory of coherent spin transitions must be incorporated in IET, as was done for different goals in refs and .…”
Section: Discussionmentioning
confidence: 99%
“…as a summer school student, allowing him to successfully work on this paper. The numerical simulations were performed with the help of a computer program, QYield, developed by E. B. Krissinel, which was previously used for studying the spin-affected reaction of forward and backward transfer in ref .…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…1−4 The mechanisms of MFEs including the hyperfine coupling mechanism, the Δg mechanism, the level-crossing mechanism, the triplet mechanism, the spin relaxation mechanism, and low-field effects have been well established by reliable experimental measurements and through the development of theory of spin dynamics, which are also associated with the generation of chemically induced magnetic polarizations. 1,4 It has been suggested and demonstrated that RP dynamics in the absence and presence of magnetic fields are rich in information not only regarding the mechanisms of MFEs 5−7 but also regarding spatial RP motions in various media such as uniform solutions, 8,9 micelles, 10−13 proteins, 14 and ionic liquids. 15,16 Transient absorption spectroscopy, in which the absorption of transient radicals can be observed with high time resolution, is surely the first choice for the direct observation of RP dynamics under magnetic fields.…”
Section: ■ Introductionmentioning
confidence: 99%